2019
DOI: 10.1007/jhep04(2019)142
|View full text |Cite
|
Sign up to set email alerts
|

Jet veto resummation with jet rapidity cuts

Abstract: Jet vetoes are widely used in experimental analyses at the LHC to distinguish different hard-interaction processes. Experimental jet selections require a cut on the (pseudo)rapidity of reconstructed jets, |η jet | ≤ η cut . We extend the standard jet-p T (jet-veto) resummation, which implicitly works in the limit η cut → ∞, by incorporating a finite jet rapidity cut. We also consider the case of a step in the required p cut T at an intermediate value of |η| 2.5, which is of experimental relevance to avoid the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…Extending jet vetoes to the forward region, 2.4 |η| 4.5, is avoided, among other reasons, to help to mitigate the contamination of pile-up activity, including the contribution to low-p T jets that would otherwise never exceed a veto threshold. This avoidance, however, is at the cost of an increased dependence on higher order QCD splittings, and hence an increased theoretical uncertainty [30]. On the other hand, it has recently been demonstrated that rapidity-dependent, jet vetoes, in particular one wherein p Veto T is relaxed for increasing jet pseudorapidity, can reduce this theoretical uncertainty [30], and are already experimentally viable [111].…”
Section: Impact Of Jet Veto Rapidity Windowmentioning
confidence: 99%
See 2 more Smart Citations
“…Extending jet vetoes to the forward region, 2.4 |η| 4.5, is avoided, among other reasons, to help to mitigate the contamination of pile-up activity, including the contribution to low-p T jets that would otherwise never exceed a veto threshold. This avoidance, however, is at the cost of an increased dependence on higher order QCD splittings, and hence an increased theoretical uncertainty [30]. On the other hand, it has recently been demonstrated that rapidity-dependent, jet vetoes, in particular one wherein p Veto T is relaxed for increasing jet pseudorapidity, can reduce this theoretical uncertainty [30], and are already experimentally viable [111].…”
Section: Impact Of Jet Veto Rapidity Windowmentioning
confidence: 99%
“…This avoidance, however, is at the cost of an increased dependence on higher order QCD splittings, and hence an increased theoretical uncertainty [30]. On the other hand, it has recently been demonstrated that rapidity-dependent, jet vetoes, in particular one wherein p Veto T is relaxed for increasing jet pseudorapidity, can reduce this theoretical uncertainty [30], and are already experimentally viable [111]. Moreover, extending dynamic jet vetoes to the forward region was found to be necessary to ensure a sufficient suppression of SM backgrounds in studies at higher √ s [42].…”
Section: Impact Of Jet Veto Rapidity Windowmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent study by Ref. [101] shows that this is a reasonable approximation for jet veto windows that extend out to η max ∼ 4.5. For jet vetoes limited to η max 2.5, the computation grows more sensitive to higher order QCD radiation [101].…”
Section: Iv11 Triplet Scalar Production With Jet Vetoes At Nlo+nnllmentioning
confidence: 76%
“…While many of these calculations have focussed on the resummation of a single logarithmic series, there has recently been a significant effort to jointly resum multiple logarithms. This includes the joint resummation of logarithms due to threshold production and transverse momentum [30][31][32][33][34][35][36], threshold and small x [37,38], transverse momentum and small x [39], transverse momentum and beam thrust [40,41], jet mass and dijet invariant mass [42,43], two angularities [44,45], jet veto and jet radius [46], jet mass and jet radius [47], jet vetoes and jet rapidity [48,49], and threshold and jet radius [50,51].…”
Section: Introductionmentioning
confidence: 99%